Endovascular Treatment of Pediatric Ischemic Stroke: a Single Center Experience and Review of the Literature - Fragata, I (2022)
Introduction: Mechanical thrombectomy is standard treatment for large vessel occlusion (LVO) in adults. There are no randomized controlled trials for the pediatric population. We report our single-center experience with thrombectomy of LVO in a series of pediatric patients, and perform a review of the literature. Methods: Retrospective review of consecutive pediatric thrombectomy cases between 2011 and 2018. Demographic variables, imaging data, technical aspects and clinical outcome were recorded. Results: In a period of 7 years, 7 children were treated for LVO at our center. Median age was 13 (2-17), and median Ped-NIHSS was 15 (3-24), and the median ASPECTS was 8 (2-10). Five patients had cardiac disease, and 2 of them were under external cardiac assistance. Median time from onset of symptoms to beginning of treatment was 7h06m (2h58m-21h38m). Five patients had middle cerebral artery occlusions. Thrombectomy was performed using a stentriever in 3 patients, aspiration in 3 patients, and combined technique in 1 patient. Six patients had good recanalization (TICI 2 b/3). There were no immediate periprocedural complications. At 3 months, 4 patients (57%) were independent (mRS score <3). Two patients died, one after haemorrhagic transformation of an extensive MCA infarct, and one due to extensive brainstem ischemia in the setting of varicella vasculitis. Discussion: Selected pediatric patients with LVO may be treated with mechanical thrombectomy safely. In patients under external cardiac assistance and under anticoagulation, thrombectomy is the only alternative for treatment of LVO. A multidisciplinary approach in specialized pediatric stroke centers with trained neurointerventionalists are essential for good results.